Ceutics sharing session: rheometer – from theory to application - Ahmad Shukri, Ahmad Assakir (Faculty of Pharmacy, 2025)
On 13 August 2025, the UiTM Faculty of Pharmacy (Faculty), in collaboration with LMS Scientific Solution Sdn. Bhd., successfully hosted the Ceutics Sharing Session: Rheometer – From Theory to Application. Held at the Seminar Room, Level 4 FF2, the fullday event brought together members of academia and privatesector professionals interested in deepening their understanding of rheology and its relevance across industries.